2016
DOI: 10.14238/sp17.4.2015.261-6
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kadar Prokalsitonin dan Kultur Bakteri dengan Tingkat Keparahan Pneumonia pada Anak

Abstract: Latar belakang. Di negara berkembang, pneumonia merupakan penyebab utama kesakitan dan kematian pada bayi dan balita. Penelitian sebelumnya menemukan prokalsitonin dapat menggambarkan keparahan pneumonia pada anak. Dilaporkan juga kultur bakteri positif lebih sering ditemukan pada pneumonia berat dengan komplikasi. Tujuan.Menentukan hubungan kadar prokalsitonin dan kultur bakteri dengan tingkat keparahan pneumonia.Metode. Penelitian potong lintang yang dilaksanakan dari bulan September 2014 hingga Januari 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Most of the children in the case group were >1 year old. Nonetheless, this finding is consistent with those reported by Suwarto et al [ 15 ] which also revealed no relationship between the age and the incidence of pneumonia in children under 5 years ( P =0.642). Muhe et al [ 19 ] and Greenberg et al [ 20 ] came to similar conclusions.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Most of the children in the case group were >1 year old. Nonetheless, this finding is consistent with those reported by Suwarto et al [ 15 ] which also revealed no relationship between the age and the incidence of pneumonia in children under 5 years ( P =0.642). Muhe et al [ 19 ] and Greenberg et al [ 20 ] came to similar conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, this finding is consistent with those reported by Suwarto et al which also revealed no relationship between the age and the incidence of pneumonia in children under five years (p = 0.642). 15) Muhe et al and Greenberg et al came to similar conclusions. We also found no relationship between sex and the incidence of pneumonia among children in our cohort, an observation that may relate to different proportions of males and females enrolled in the study 19), 20) .…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 62%
See 2 more Smart Citations